(untitled) (Global Journal of Human-Social Science, 2019)
Corrosion inhibition of copper alloy in 0.3 M HNO and KOH at room temperature using Mangiferaindica leaf extract in different concentrations was studied. A Gravimetric technique was employed. The result obtained showed that Mangiferaindica leaf extract is a good inhibitor for 0.3 M HNO 3 and KOH solution. The weight loss, corrosion rate, and inhibition efficiency were deduced. The inhibition efficiency showed a good percentage result with the optimum value of 85.60% and 90.91% in HNO 3 and KOH respectively. Generally, it was observed that the rate of inhibition increased with the concentration of the inhibitor decreased in corrosion rate.